Monte-Carlo Simulation und Due Diligence: Ein methodischer Ansatz zur computergestützten Aggregierung von Wahrscheinlichkeitsverteilungen aus Expertenbefragungen - Martin Klein (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Rechnungswesen und Prüfungswesen, 2010)
– The combination of experts' probability distributions involved in a due diligence is valuable for encapsulating the accumulated information for decision makers and providing the current state of expert opinion regarding important uncertainties. Therefore, this paper shows how to create and combinate experts' probability distributions which can be used in a monte-carlo simulation to calculate company values.
http://hdl.handle.net/10419/30190
Keywords: C80; G17; G32; G34; 650; Unternehmensbewertung; Due Diligence; Monte-Carlo Simulation; Delphi-Methode; Szenarioanalyse; Sensitivitätsanalyse; Expertenbefragung; Wahrscheinlichkeitsverteilung; Simulationssoftware; valuation; due diligence; monte-carlo method; simulation; business forecast; forecast uncertainty; scenario analysis; sensitivity analysis; probability distribution; combining probabilities; expert judgment; Unternehmensbewertung; Computergestütztes Verfahren; Monte-Carlo-Methode; Delphi-Technik; Szenario-Technik